Percutaneous Closure of Post-myocardial Infarction Ventricular Septal Rupture-experience From a Resource-limited Setup From Eastern Part of India - Saha, Siddhartha (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: Post-infarction ventricular septal rupture (VSR) is a rare but lethal mechanical complication of an acute myocardial infarction (AMI). It results in 90% - 95% mortality within two months of diagnosis without any kind of intervention. Given high surgical mortality, transcatheter closure has emerged as a potential strategy as an alternative to high-risk surgical closure. Indian data on percutaneous device closure of post-AMI-VSR is limited hence we report our resource-limited single-centre experience with different kinds of occluder devices for closure of post-AMI VSR. Methods and results: In this single-centre, retrospective, cohort study, patients who underwent transcatheter closure of post-MI VSR between 2018 and 2024 at Health World hospitals, in Durgapur, West Bengal, were included. The primary outcome was a mortality rate of 30 days. The study population was eleven primary cases of post-MI VSR. The mean age of the population was 61 years. The majority of the patients had anterior wall MI (54.5%) and the remaining had inferior wall MI. Different kinds of devices (ASO, PostMI VSD device, Konar MFO) were used to close VSR. Successful closure was performed in 9 patients (81%) with minimal residual shunt in 2 patients. Out of 9 cases 3 patients expired, one was lost to follow up and the rest are doing well at 30 days follow-up. Conclusion: Transcatheter closure of PMIVSRs can be performed with different kinds of devices with high technical success, relatively low procedural complication rates, and 30 days survival even in a resource-limited setup as an alternative to high-risk surgical closure.